Pseudoshasticrioceras bersaci nov. sp. (Ammonoidea, Gassendiceratinae), and new ammonite biohorizon for the Upper Barremian of southeastern France - Bert Didier; Delanoy Gérard (Carnets de Géologie, 2009)
Research in the Feraudianus Subzone of the Sartousiana Zone of the Barremian stage led to the discovery of a new species of Pseudoshasticrioceras: P. bersaci nov. sp. Its study provides evidence concerning the developments of the latest Gassendiceratinae Bert et alii, 2006, and the relationship between the genus Pseudoshasticrioceras Delanoy, 1998, and Gassendiceras Bert et alii, 2006. In particular, this new species is derived from Pseudoshasticrioceras magnini (Delanoy, 1992) by a minor revision in the processes of ontogenesis (retardation of ornamentation - neoteny). However, the evolution towards Pseudoshasticrioceras autrani Delanoy, 1998, implies a "failure" in this process that may possibly be related to parallel changes in environmental conditions. On the other hand, the very closely defined stratigraphic position of Pseudoshasticrioceras bersaci nov. sp., and its position in the anagenetic lineage of Pseudoshasticrioceras, demonstrates its interest as a biostratigraphic marker: a new Bersaci Biohorizon is proposed; it is located between the Magnini and the Autrani biohorizons.